2004
DOI: 10.3354/meps281093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the northern quahog Mercenaria mercenaria on the development of blooms of the brown tide alga Aureococcus anophagefferens

Abstract: Three experiments were carried out in 300 l mesocosms using natural seawater from the Peconic Bays ecosystem, Long Island, New York, to examine the ability of the northern quahog Mercenaria mercenaria to prevent blooms of the brown tide alga Aureococcus anophagefferens. Nutrient enrichment and mixing of the mesocosms was conducted according to previous methods that we have employed to induce brown tides. Treatments with and without clams were examined. Abundances of A. anophagefferens increased dramatically du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…2). There was no correlation between the presence of hard clams and sediment characteristics, perhaps due to low overall abundances of hard clams, which were a fraction of those found in this system decades ago (Cerrato et al 2004). Sediment characteristics within the eelgrass beds were significantly different from those outside.…”
Section: Field Surveymentioning
confidence: 78%
See 2 more Smart Citations
“…2). There was no correlation between the presence of hard clams and sediment characteristics, perhaps due to low overall abundances of hard clams, which were a fraction of those found in this system decades ago (Cerrato et al 2004). Sediment characteristics within the eelgrass beds were significantly different from those outside.…”
Section: Field Surveymentioning
confidence: 78%
“…One individual (~5 cm valve length) was added to the center of each plot. This yielded a clam density of 16 m -2 , which is higher than current clam densities in LISSE, but considerably lower than historical densities (Cerrato et al 2004). Another 10 plots were randomly assigned to the fertilized treat-ments and received a single Miracle-Gro ® Tree & Shrub Fertilizer spike to the center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesocosm experiments have shown that filtration of A. anophagefferens cells at low densities by hard clams may prevent the development of brown tide outbreaks (Cerrato et al, 2004), which reduce eelgrass production via light attenuation. Nutrient enrichment of sediments by bivalve biodeposits can facilitate eelgrass productivity, given that Z. marina absorb most of their nutrients from sediments via their roots rather than from the water column (Peterson and Heck, 1999).…”
Section: Submerged Aquatic Vegetation (Sav)mentioning
confidence: 99%
“…Many of these algal blooms can be linked to eutrophication (Anderson et al 2008, Heisler et al 2008 or loss of benthic filtration (Newell 1988, Lotze et al 2006. Benthic suspension feeders can filter the water column quickly enough to suppress blooms of phytoplankton in some systems (Officer et al 1982, Cerrato et al 2004, Wall et al 2008, and such top-down control should be more prevalent in ecosystems that are shallow and have a high density of consumers (Smaal & Prins 1993, Heck & Valentine 2007, such as shallow coastal lagoons. Since coastal lagoon systems often have extended physical turnover times, which makes them more vulnerable to harmful micro-algal blooms (Cloern 2001), the loss of benthic suspension feeders from such a system likely represents a more significant loss of top-down control than for deeper, well-flushed ecosystems.…”
Section: Introductionmentioning
confidence: 99%